Urbanization and Climate Resilience: How is Vulnerability and Poverty in Makassar - Anirwan Anirwan (Journal of Governance, 2023)
This article examines how the processes of urbanization and climate resilience are related to vulnerability and poverty. This article aims to determine the correlation between climate resilience, vulnerability, and poverty. From a methodological point of view, this is qualitative research using the collection of documents, such as the Regional Action Plan for Climate Change Adaptation-Disaster Risk Reduction (RAD API-PRB) and documents from government websites. The findings of this study illustrate that urbanization followed by development impacts land-use change. Land degradation due to urbanization and climate change will have direct human impacts due to extreme events and increased vulnerability, with significant environmental, economic, and social consequences for communities, particularly the poorest communities, who are most vulnerable. We suggest developing ways to reduce vulnerability through strategic management planning to reduce exposure to stress, sensitivity, and adaptive capacity.